PENGARUH TGT BERBANTUAN MEDIA MONOPOLI ELEKTRONIK TERHADAP HASIL BELAJAR DARING KELAS IV SDN 1 PATOKPICIS MALANG - Yuninda Dewi Agustin; Nury Yuniasih; Dyah Tri Wahyuningtyas (Indonesian Journal of Elementary Education (IJOEE), 2021)
The implementation of online learning teachers is very dominant in carrying out learning, the media used is less attractive, so that students are less enthusiastic in learning activities and have an impact on decreasing learning outcomes. This study aims to determine the effect of the TGT model assisted by Electronic Monopoly media (ME 3IN1) on the learning outcomes of fourth grade students. The approach used is quantitative research, with the type of quasi-experimental research. The research sample IVA and IVB amounted to 50 students. The research instrument used tests in the form of pre-test and post-test. The independent variable in this study is the TGT model and electronic monopoly media while the dependent variable is student learning outcomes. The research subjects were students IV SDN 1 Patokpicis Malang. Based on the results of hypothesis testing, a significance value of 0.00 <0.05 is obtained so that Ho is rejected, H1 is accepted, so it can be concluded that there is an effect of TGT assisted by electronic monopoly on learning outcomes. In addition, the increase in learning outcomes in the experimental class was 13 from the average value of pre-test 67 and post-test 80.Keywords: online learning, electronic monopoly (ME 3IN1), learning outcomes, thematic